The Protection Of Geographical Indications In Malaysia - Tay, Pek San (Journal of Malaysian and Comparative Law, 2019)
Many expressions used on goods in the course of trade encompass geographical terms. Expressions such as "Langkwai Marble", "Thai fragant rice", "Indonesian teak furniture", "Japanese green tea", "Korean ginseng", "Western Australian honey", "Californian prunes", "Swiss watch" and "Swiss chocolates" are but a few of the numerous geographical terms used on goods in commerce.